Students’ Mathematical Critical Thinking Ability: Influenced by Edpuzzle Assisted Problem Based Learning (PBL) Model - Faradillah, Ayu; Sabella Putri (Universitas Pendidikan Ganesha, 2024)
The current problem is that students' critical thinking skills are relatively low. This low ability is because students memorize materials and formulas rather than understand concepts. In addition, students' mathematical critical thinking skills in analyzing a problem are relatively low. This study aimed to analyze the effect of using the PBL model assisted by Edpuzzleon on students' mathematical critical thinking skills. This study uses a quantitative method. The research design used is a post-test-only control. The sampling technique used was simple random sampling with 69 students. The data collection method uses a test. The data collection instrument uses a test instrument. Validity and reliability tests were carried out in data collection using WinSteps 3.73, and all instrument indicators were declared valid and reliable. Data analysis test on SPSS 26. The study showed that the effect size test was 1.06 with high criteria. The use of the PBL model with edpuzzle affects mathematical critical thinking skills. It is concluded that the PBL model with edpuzzle can improve mathematical critical thinking skills. This research implies that it can provide insight for teachers in treating students' critical thinking skills.